Optimizing Engagement in Behavioral Parent Training: Progress Toward a Technology-Enhanced Treatment Model() - Jones, Deborah J. (Behav Ther, 2021)
Low-income families are more likely to have a child with an early-onset Behavior Disorder (BD); yet, socioeconomic strain challenges engagement in Behavioral Parent Training (BPT). This study follows a promising pilot to further examine the potential to cost-effectively improve low-income families’ engagement in and the efficiency of BPT. Low-income families were randomized to (a) Helping the Noncompliant Child (HNC; McMahon & Forehand, 2003), a weekly, mastery-based BPT program that includes both the parent and child or (b) Technology-Enhanced HNC (TE-HNC), which includes all of the standard HNC components plus a parent mobile application and therapist web portal that provide between-session monitoring, modeling, and coaching of parent skill use with the goal of improved engagement in the context of financial strain. Relative to HNC, TE-HNC families had greater homework compliance and mid-week call participation. TE-HNC completers also required fewer weeks to achieve skill mastery and, in turn, to complete treatment than those in HNC without compromising parent satisfaction with treatment; yet, session attendance and completion were not different between groups. Future directions and clinical implications are discussed.